Perancangan TPS Cipapais sebagai Sarana Pengelolaan Sampah di Kelurahan Kadumerak, Kecamatan Karang Tanjung, Kabupaten Pandeglang - Alifah Fidela; Heriansyah Putra; Nurul Chairunnisa; Fikha Raihani; Fazrina Andriani Sakinah Lubis; Muhammad Adhiragil Kandyas; Larasaty; Risma Amelia; Giri Rasyidpradana Ganda (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
The design of the Cipapais Temporary Waste Disposal Site (TWDS) in Kadumerak village, Karang Tanjung district, Pandeglang aims to solve the waste problem in Cipapais Village through regular and efficient waste management by applying household scale of waste sorting. The TWDS is made based on research on the generation and composition of waste in Cipapais Village. This research is conducted for eight days by measuring the weight and volume of waste which collected from houses and shops (nonhome). The results showed that Cipapais TWDS needs an area of 27 m2 . The TWDS is equipped with a warehouse, sorting room, and a garbage disposal place equipped with a container foundation. Trash every home is scheduled to be transported using two hand carts to TWDS every day. TWDS waste is scheduled to be moved twice a week to Bangkonol Final Processing Site (FPS) using one unit of 6 m3 dump truck. The design of the existing TWDS is expected to be realized by continuous communication between Kadumerak Village, Environment Service of Pandeglang and the Cipapais Village community. Keywords: TWDS, waste composition, waste generation, waste management, waste transport